Joá yellow blotch-associated virus, a new alphanucleorhabdovirus from a wild solanaceous plant in Brazil - Dietzgen, Ralf Georg (2021)
We identified a novel plant rhabdovirus infecting native joá (Solanum aculeatissimum) plants in Brazil. Infected plants showed yellow blotches on the leaves, and typical enveloped bacilliform rhabdovirus particles associated with the nucleus were seen in thin sections by electron microscopy. The virus could be graft-transmitted to healthy joá and tomato plants but was not mechanically transmissible. RT-PCR using degenerate plant rhabdovirus L gene primers yielded an amplicon from extracted total RNA, the sequence of which was similar to those of alphanucleorhabdoviruses. Based on close sequence matches, especially with the type member potato yellow dwarf virus (PYDV), we adopted a degenerate-primer-walking strategy towards both genome ends. The complete genome of joá yellow blotch-associated virus (JYBaV) is comprised of 12,965 nucleotides, is less than 75% identical to that of its closest relative PYDV, and clusters with PYDV and other alphanucleorhabdoviruses in L protein phylogenetic trees, suggesting that it should be taxonomically classified in a new species in the genus Alphanucleorhabdovirus, family Rhabdoviridae. The genome organization of JYBaV is typical of the ‘PYDV-like’ subgroup of alphanucleorhabdoviruses, with seven genes (N-X-P-Y-M-G-L) separated by conserved intergenic regions and flanked by partly complementary 3' leader and 5' trailer regions.